PENGUKURAN KESEIMBANGAN LINTASAN PRODUKSI SABUK KOPLING MOBIL - Akhsani Nur Amalia; Darmawan Yudhanegara; Agung Gumelar (Industrika : Jurnal Ilmiah Teknik Industri, 2021)
Time efficiency in production is very supportive of fulfilling consumer demand. The track balance problem can be solved by taking measurements first. This measurement aims to determine the parameters that cause an imbalance in the production line. The first step that needs to be done is measuring the track balance before optimization. Rank Postional Weight is heuristic’s systematic approach method is used to measure the balance of the car CVT belt production line in a grinding machine. The measurement results show that it is not good with a smothness index of 130.48 minutes, the product produced is only 97.5% of the set target, the performance of the work station is 80.56%. Improvements in several work stations in order to improve the balance of the trajectory, namely in visual checks, smoothing surfaces and shapes, measuring products by rearranging the order.